The Sicilian : a novel - Puzo, Mario, 1920-1999 (Ballantine Books, 2004)
"Turi Guilliano works to enhance his romantic image, but in the mid-1940s the Sicilian Mafia forces him to escape to the American Mafia, in the sequel to The Godfather"--NoveList.